Digital preservation: The conduit through which open data, electronic government and the right to information are implemented. Issue 4 (21st November 2016) - Adu, Kofi Koranteng; Dube, Luyande; Adjei, Emmanuel
Abstract : Purpose: The purpose of this paper is to explore the extent to which digital preservation facilitate the implementation of electronic government, open data and the right to information. Design/methodology/approach: A case study research which chronicles the link between transparency and data availability. It makes use of a theoretical framework based on the open archival information system to analyse, explain, clarify and justify the application of open data, electronic government and the right to information. Findings: The paper argued that e-government, open data and the RTI will remain elusive if a digital preservation infrastructure is not pursued. Within the context of e-government, the paper adumbrated that government agencies can incorporate e-government legislations into their digital preservation activities, precisely because the relationship between digital preservation and e-government have always been symbiotic. It alluded to the fact that an obligation will be placed on all public authorities and private agencies covered by the RTL law to create, keep and organise an effective and efficient system of record keeping, so as to give meaning to the right to information when citizens apply for information. Practical implications: Future research should examine closely the implication of open data government within the context of digital preservation. Whilst digital preservation looks forward to the longevity of digital records and its accessibility, open data focusses on the utility of these records through online services, reuse and distribution for the purposes of transparency and citizens' participation. Originality/value: The application of digital preservation to open data in this paper appears to be more relevant at a time when most governments of the world are striving to obtain data to fight poverty, achieve universal primary education, fight HIV and foster maternal health. Its originality can further be established from the symbiotic relationship between digital preservation and electronic government, open data and the right to information.